Comparative Environmental Impacts of Biotechnology-derived and Traditional Soybean, Corn, and Cotton Crops - Carpenter, Janet; Felsot, Allan; Goode, Timothy; Hammig, Michael; Onstad, David; Sankula, Sujatha (Council for Agricultural Science and Technology (CAST), 2002)
A comprehensive review of the scientific literature supports the conclusion that overall the currently commercialized biotechnology-derived soybean, corn, and cotton crops yield environmental benefits. Furthermore, a critical analysis of the literature supports the idea that biotechnology-derived soybean, corn, and cotton pose no environmental concerns unique to or different from those historically associated with conventionally developed crop varieties.